2017
DOI: 10.24059/olj.v21i3.866
|View full text |Cite
|
Sign up to set email alerts
|

Revised Community of Inquiry: Examining Learning Presence in a Blended Mode of Delivery

Abstract: This paper presents a study grounded in the Community of Inquiry (CoI) framework using qualitative content analysis and focus group interviews in an effort to identify aspects of learning presence in a blended learning course. Research has suggested that the CoI framework may need additional emphasis based on the roles of strategic learners in online environments. Consequently, this qualitative study investigated the extent to which learning presence, the fourth presence of the CoI framework, manifested itself… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 13 publications
3
42
0
3
Order By: Relevance
“…The students noted in the survey that they disagreed strongly with the use of an online platform for social interaction, possibly due to their preference for physical presence of their nursing tutors for learning. (Pool et al, 2017). Therefore, it is crucial that students are given sufficient guidance and time to navigate the online platform in the beginning of the module to familiarise themselves with the features and be comfortable with interacting with other students on the platform.…”
Section: Discussionmentioning
confidence: 99%
“…The students noted in the survey that they disagreed strongly with the use of an online platform for social interaction, possibly due to their preference for physical presence of their nursing tutors for learning. (Pool et al, 2017). Therefore, it is crucial that students are given sufficient guidance and time to navigate the online platform in the beginning of the module to familiarise themselves with the features and be comfortable with interacting with other students on the platform.…”
Section: Discussionmentioning
confidence: 99%
“…The ANOVA revealed that the difference in mean score was statistically significant between undergraduate and graduate students for each of the three dimensions of the CoI framework. Given that online learning requires higher levels of self-regulation than in-person courses (Pool, Reitsma, & van den Berg, 2017), graduate students may have sophisticated learning skills to address any barriers and the independence to confront feelings of isolation often experienced in online learning environments (Clark, Strudler, & Grove, 2015;Tsai, 2007). Since undergraduate students may not have sufficient social support and subsequent difficulty dealing with stress (Ickes, Brown, Reeves, & Martin, 2015), and maturity for post-secondary education in general, it is not surprising that undergraduate students' may not be ready for a foyer into the independence and rigour called for in online post-secondary courses.…”
Section: Is There a Difference In Perceptions Towards The Three Dimenmentioning
confidence: 99%
“…Participants underwent individual, semi-structured audio-recorded, telephonic interviews. Two sets of six open-ended questions, each for students and facilitators, were designed on the basis of Revised Garrison Community of Inquiry framework, which has been developed as a means to investigate effective online and blended learning environments in higher education 8. After pilot testing, the participants were approached, and informed consent was taken.…”
Section: Methodsmentioning
confidence: 99%